The mixing regime of Lake Ammersee - Bueche, Thomas (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
Climate change affects the circulation of lakes and has already induced mixing regime shifts for 9 several sites. The pre-alpine Lake Ammersee, Germany, is usually dimictic, but exhibits rarely a 10 complete ice cover. Furthermore, it has potentially shown some monomictic years in the past. Based 11 on vertical profile data of water temperatures (WT) and dissolved oxygen (DO) the mixing behavior 12 of the lake is visualized and analyzed for the period of 1986 – 2014. The classification of mixing 13 depicts 22 dimictic years and eight monomictic years, which approves the assumption of of 14 occasional monomixis in the lake. No significance of a trend of shift in mixing pattern can be found. 15 By also deriving also the mixing depths from the vertical DO distribution, one year without complete 16 overturn (meromictic) is detected. The results show that no regime shift has set in for Lake 17 Ammersee until 2014. Considering the high percentage of monomictic years and the potential 18 occurrence of meromixis, it can be assumed that the lake’s mixing pattern will alter due to predicted 19 climate change in the future.